Factors Limiting Employee Innovativeness - Pietroń-Pyszczek, Agata (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The basic premise of the article is the claim that every new employee beginning their career in a given organization, has a certain amount of innovative potential. The organization can and should use that potential, which, as empirical research shows, is not a rule. An attempt has been made to demonstrate which internal factors are significant barriers to the development of innovative attitudes and behaviours of employees. The focus was on management issues. Employee innovativeness is an important context of management, explaining mechanisms of growth and development of the organization.